The Ethics of Global Supply Chains in China – Convergences of East and West - Krueger, David A. (Journal of business ethics, 2008)
This paper addresses ethical issues surrounding global supply chains of multinational companies in developing countries. In particular, it considers the development and application of industry-wide ethical standards and codes of conduct for multinational supply chains in China. We describe and analyze the ethical norms and compliance components of such industry-wide regimes in the toy, textile, and consumer electronics industries. We argue that this development represents an positive attempt to institutionalize emergent international ethical standards and practices into this component of the Chinese economy.